Avaliação da iluminação natural em edificação de uso coletivo em Cascavel - Corredato, Aryon Pugsley; Siqueira, Jair Antonio Cruz; Nascimento, Laís Fernanda Juchem do; Cruz, Nayara Fernanda Ferraz da Silva; Tokura, Luciene Kazue; Villa, Bruna de (Latin American Journal of Energy Research, 2021)
Brazil is a country with a good incidence of sunlight throughout the year, so buildings that present the maximum use of daylighting, ensuring greater comfort and energy efficiency are one of the premises of sustainable architecture. Following this line of thought, the need for more in-depth studies regarding the better use of daylight and the use of ventilation in buildings is evident. In order for future projects to make better use of daylighting, flaws must be analyzed, studied, and understood, and evidence of the adjustments made in the design of current buildings. The present work aimed to evaluate the levels of natural illuminance maintained inside a residential building for collective use in Cascavel - PR and to compare them to the minimum values ​​established by current regulations. The study was developed based on measurements of the level of daylighting in 3 apartments on different floors, each with a different orientation, using the methodology proposed by the Brazilian Association of Technical Standards. Subsequently, a comparison was made with the data obtained in the study with the minimum values ​​suggested by the current rules. The apartments had daylight levels in accordance with the standard, in 7 of the 8 rooms studied. Only the BWC 1 room did not reach the minimum levels recommended by the standards, due to the fact that it does not have a window that allowed daylight to enter.